MUC17 Is a Potential New Prognostic Biomarker and Promotes Pancreatic Cancer Progression in Obstructive Jaundice - Gál, Eleonóra; Menyhárt, István; Veréb, Zoltán; Kemény, Lajos; Tiszlavicz, László; Köhler, Zoltán Márton; Keller-Pintér, Anikó; Rakk, Dávid; Szekeres, András; Takács, Tamás; Czakó, László; Hegyi, Péter; et al. (Oncology, 2025)
AbstractIntroduction: Our working group has previously shown that bile acids (BAs) accelerate carcinogenic processes in pancreatic cancer (PC) in which mucin 4 (MUC4) expression has a central role. However, the role of other mucins in PC is less clear, especially in bile-induced cancer progression. The study aim was to investigate expression of MUC17 in BA- or human serum-treated pancreatic ductal adenocarcinoma (PDAC) cell lines. Methods: Different cell-based assays with RNA silencing/overexpression were used to study the role of MUC17 in cancer progression. Protein expression of MUC17 was evaluated in 55 human pancreatic samples by immunohistochemistry, and Kaplan-Meier survival analysis was used to compare survival curves. Results: Expression of MUC17 increased in PDAC patients, especially in obstructive jaundice (OJ), and the elevated MUC17 expression associated with poorer overall survival (10.66 ± 1.99 vs. 15.05 ± 2.03 months; log-rank: 0.0497). Treatment of Capan-1 and AsPC-1 cells with BAs or with human serum obtained from PDAC + OJ patients enhanced the expression of MUC17, as well as the proliferative potential of the cells, whereas knockdown of MUC17 alone or in combination with MUC4 decreased BAs-induced carcinogenic processes. Conclusion: Our results demonstrated that MUC17 has a central role in bile-induced PC progression, and in addition to MUC4, this isoform also can be used as a novel prognostic biomarker.